Предмет: Алгебра, автор: zekrompoke2

пж помогите с примерами ​

Приложения:

Ответы

Автор ответа: Miroslava227
1

Ответ:

1) {2}^{x - 3}  =  {3}^{ - (x - 3)}  \\  {2}^{x - 3}  =   {( \frac{1}{3} )}^{x - 3}  \\  {(2 \times 3)}^{x - 3}  = 1 \\  {6}^{x - 3}  =  {6}^{0}  \\ x - 3 = 0 \\ x = 3

2) {3}^{x} ( {3}^{3}  + 1) =  {7}^{x}(7 + 5) \\  {3}^{x}   \times 28 =  {7}^{x}  \times 12 \\  { (\frac{3}{7} )}^{x}  =  \frac{12}{28}  \\  {( \frac{3}{7} )}^{x}  =  \frac{3}{7}  \\ x = 1


zekrompoke2: да благословит вас бог, спасибо огромное
Похожие вопросы